2012
DOI: 10.1016/j.vaccine.2012.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles (OMV) production of Neisseria meningitidis serogroup B in batch process

Abstract: Serogroup B outer membrane vesicles (OMV) with iron regulated proteins (IRP) from Neisseria meningitidis constitute the antigen for the vaccine against the disease caused by this bacterium. Aiming to enhance final OMV concentration, seven batch experiments were carried out under four different conditions: (i) with original Catlin medium; (ii) with original Catlin medium and lactate and amino acids pulse at the 6th cultivation hour; (iii) with Catlin medium with double initial concentrations of lactate and amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
10
0
5
Order By: Relevance
“…Most early publications connect OMV formation with cell growth, since bleb formation was not observed in the stationary phase [87, 88], and cells growing at exponential phase produced more OMVs [79, 89]. The pattern is now mixed, with higher release of OMVs during late culture phase reported for N. meningitidis [90] and Francisella [91], while Salmonella typhimurium [73, 92], Borrelia [93], and Gallibacterium [94] seem to produce more vesicles during exponential growth. For H. pylori the release of OMVs is inversely related to the cell growth and is also correlated with shape transitions of the bacterium from spiral to coccoid [22].…”
Section: Natural Omvmentioning
confidence: 99%
See 1 more Smart Citation
“…Most early publications connect OMV formation with cell growth, since bleb formation was not observed in the stationary phase [87, 88], and cells growing at exponential phase produced more OMVs [79, 89]. The pattern is now mixed, with higher release of OMVs during late culture phase reported for N. meningitidis [90] and Francisella [91], while Salmonella typhimurium [73, 92], Borrelia [93], and Gallibacterium [94] seem to produce more vesicles during exponential growth. For H. pylori the release of OMVs is inversely related to the cell growth and is also correlated with shape transitions of the bacterium from spiral to coccoid [22].…”
Section: Natural Omvmentioning
confidence: 99%
“…The detergent D‐OMVs, are extracted from cells with detergent which also reduces the content of reactogenic LPS. The term native N‐OMV is used for intact spontaneous OMVs from cell supernatant [40], as well as for OMVs that are generated from concentrated dead cells with non‐detergent cell disruption techniques [90, 112]. Here, native N‐OMV will be used for vesicles extracted from cells with detergent–free methods, in accordance with previous nomenclature, and to be able to clearly distinguish them from the wild‐type spontaneous OMVs and the detergent‐extracted OMVs.…”
Section: Omvs Vaccine Developmentmentioning
confidence: 99%
“…Santos et al [40, 41] studied the consumption of aminoacids in Catlin defined medium during batch process of N. meningitidis B and observed that L-lactate and L-glutamic were the main limiting carbon and nitrogen source, respectively. The L-glutamic acid consumption contributed to the formation of ammonia and the increase of pH during in cultivations and L-cysteine.HCl had small consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Foram escolhidas neste trabalho as condições de cultivo e os meios de cultura que obtiveram melhores resultados de biomassa e concentração de OMV, em cultivo descontínuo, com base em trabalhos desenvolvidos anteriormente (GONÇALVES, 2012;SANTOS et al, 2012) Destaque em cinza para os valores máximos de DO 540nm e OMV.…”
Section: Cultivosunclassified